OPTIMASI SEDIAAN GUMMY CANDY PARASETAMOL DENGAN VARIASI KONSENTRASI GELATIN DAN GLISERIN MENGGUNAKAN METODE SIMPLEX LATTICE DESIGN - Nisa, Zaitun; Aisiyah, Siti; Purwaningsih, Desi (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2022)
Paracetamol gummy candy is a chewy candy that is composed of a mixture of sweeteners and hydrocolloid components containing paracetamol and is designed to crumble and melt on the tongue. This study aims to see the effect of variations in the concentration of gelatin and glycerin on the physical quality of paracetamol gummy candy preparations, and to determine the best concentration of gelatin and glycerin to obtain paracetamol gummy candy preparations with optimum physical properties. Preparation of the preparation using the casting method and using 8 formula designs from Design Expert Simplex Lattice Design with a ratio of gelatin and glycerin concentrations. The results of the physical quality test with the critical parameters of elasticity and moisture content were analyzed using the Simplex Lattice Design method. This method can be used to optimize the dosage formula in various variations in the amount of material composition, so as to produce the optimum formula with the expected physical characteristics. The results showed that gelatin had more effect on elasticity and glycerin had more effect on the water content of paracetamol gummy candy. The proportions of gelatin 998,723 mg and glycerin 51.277 mg resulted in the optimum formula with the best elasticity and water content of gummy candy paracetamol.